Socio-demographic, economic and mental health problems were risk factors for suicidal ideation among Kenyan students aged 15 plus - Ndetei, David M.; Mutiso, Victoria N.; Weisz, John R.; Okoth, Consolate A.; Musyimi, Christine; Muia, Esther N. (Journal of Affective Disorders, 2022)
Background: About a third of youth with suicidal ideation develop suicidal plans and about 60% of youth with suicidal plans make suicidal attempts. This study aimed to study different types of suicidal ideation and the risk factors in Kenyan youth. Methods: We studied a total of 9742 high school, college and university students using following selfadministered instruments: - a researcher design socio-demographic questionnaire, Psychiatric Diagnostic Screening Questionnaire (PDSQ) to document psychiatric disorders and various types of suicidal ideas in previous two weeks, Washington Early Recognition Center Affectivity and Psychosis tool to assess stress, affectivity and psychosis, Wealth index questionnaire to document economic indicators based on household items for the families of the students. We used descriptive statistics, univariate analysis, bivariate logistic regression analysis and variables with a p-value of less than <.05 were entered into generalized linear models using logit links to identify independent predictors. Results: The overall prevalence of different types of suicidal ideation was (22.6%), major depression was found in 20.0%, affectivity, psychosis and stress was found in 10.4%, 8.7% and 26.0% respectively. Female gender, major depression, stress, affectivity and psychosis and being in high school were significant (p < 0.05) predictors of suicidal ideation. Limitations: This was a cross sectional study that focused only on suicidal ideas and associated economic factors and mental health disorders. It did not study suicidal behavior. Conclusion: Future studies are needed to study the progression from suicidal ideas to suicidal attempts and the factors associated with that progression.
Keywords: Different types of suicidal ideas; Risk factors; Students; Kenya